Analisa Kesesuaian Lubang Resapan Biopori Sebagai Pengendali Aliran Permukaan Dari Lahan Non Gedung - Kiki Rizky Amalia; Radius Pranoto; Arfan Hasan; Ananda Ayu Putri (Universitas Batanghari Jambi, 2023)
Indonesia has the potential for high rainfall with an average of 2000-3000 mm/year. However, the potential for rain often causes many problems, such as; runoff, inundation, erosion and flooding. Biopore infiltration holes are one of the rainwater conservation technologies that have been widely applied to reduce surface runoff and increase groundwater reserves. This study aims to analyze the suitability of biopore infiltration holes in controlling runoff from open land (non-building) in the State Polytechnic of Sriwijaya, Soil seepage ability was measured using a double ring infiltrometer and obtained a value of 0.869 m/day. Model of the biopore infiltration hole used is cylindrical, 10 cm in diameter and 0.5 - 1 m deep. Simulations were carried out per area using daily rainfall data for 12 years (2007-2018). The simulation results show that the biopore infiltration hole has a water absorption capacity of 0.00298 m3/day. The ratio of the average requirement for biopore holes for open land (non-building) is 1 biopore hole per 1 m2 land area.